1999
DOI: 10.1007/s004180050429
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Kir2.0 proteins in the rat cerebellum and hippocampus by polyclonal antibodies

Abstract: Rabbit polyclonal antibodies were raised to rat Kir2.0 (Kir2.1, Kir2.2 and Kir2.3) inwardly rectifying potassium ion channel proteins. The antibody specificities were confirmed by immunoprecipitation of [35S]-methionine-labelled in vitro translated channel proteins and western blotting. Immunohistochemistry revealed a different patterns of expression of Kir2.0 subfamily proteins in the rat hind-brain (cerebellum and medulla) and fore-brain (hippocampus). Notably, only Kir2.2 protein was detected in the cerebel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 23 publications
5
48
0
Order By: Relevance
“…As an added complication, it is possible that K ir 2.2 exists as a heteromultimer with K ir 2.1 (25). Although K ir 2.3 may not contribute much to I K1 in the heart, its location in neurons (26,27) raises the possibility of a role in ischemia-induced excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…As an added complication, it is possible that K ir 2.2 exists as a heteromultimer with K ir 2.1 (25). Although K ir 2.3 may not contribute much to I K1 in the heart, its location in neurons (26,27) raises the possibility of a role in ischemia-induced excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…17 Immunoprecipitates were subjected to SDS-PAGE 18 on 7 % polyacrylamide mini gels for 1.5 h at 120 V.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…17 HEK 293 cell transfection routinely. Cells were maintained in minimal essential medium with Earle's Salts supplemented with 10% foetal calf serum and 5% L-glutamine under antibiotic selection (SUR2A, 727 µg/ml G418; Kir6.2/SUR2A, 727 µg/ml G418, 364 µg/ml zeocin).…”
Section: Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Kir2.3 binds to PSD-95, which scaffolds various functional proteins at the postsynaptic membrane of asymmetric synaptic junctions (5,7,23,30). Although these results suggest that Kir2.3 is localized at the postsynaptic membrane of excitatory synapses, light microscopy indicated that neuronal Kir2.3 distributes diffusely in the nuclei and on the plasma membrane of pyramidal cells in the CA3 region of rat hippocampus (33). To resolve this paradox, we produced a polyclonal antibody specific to Kir2.3 and examined the localization of the channel protein in mouse brain at light-and electron-microscopic levels.…”
mentioning
confidence: 88%